Distribution Sediment Fire Coal Power Plant Batang Cental Java - Krisna, Candra Nardo (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2021)
Pltu Batang or central java project power plant (CJPP) is a critical coal fire power plant with 2x1000 MW capacity in Batang regency, Central java. Construction of  apower plant in Batang regency is expected to be able to supply house hold and industrial electricity in Central java. The role of power plant is very important there fore the sediment distribution in this area must be considered in order to maintain smooth operation of the power plants activities. The studies of sediment distribution in this case study used discriptive methods, descriptive methode are methods research to create a description of a situation or event researched and studied in a limited time and in a certain place to get a overview of the situation and conditions study area. Observations of oceanographic parameter such as wind, sea floor topography, and current which a natural symptoms interrelated in the process of erosion and sedimentation, to get basic information sediment distribution and to determine how much impact the current on the basic sediment distribution fire coal power plant batang. Type tidal in this research semi diurnal tide, mean sea level value 60.014 Cm using admilarty calculation, average thickness sediment on December – February 2017 13.588 CM, average thickness sediment on March – May 2017 6.026 CM, average thickness on June – August 2017 8.783 Cm. Average thickness Sept – Nov 2017 1.217 Cm